Analysis of Marketing Strategy Phenomena on Influencers in Influencing Buyer Decisions at Shopee - Nurlaila Syarfiah Asfo; Hasbiah; Wilda Widiawati; Agus Surya Bharmawan; Rully Arifiansyah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
In today's digital era, influencer marketing has become one of the main strategies in e-commerce, including on the Shopee platform. This study aims to analyze the effect of influencer marketing strategies on consumer purchasing decisions at Shopee, with a focus on the effectiveness of Live Shopping, Product Reviews, and Discounts / Promo Codes. The research method used is quantitative with a descriptive and correlational approach. Data was collected through a survey of 385 respondents who had made a purchase after seeing an influencer promotion. The results showed that the Live Shopping strategy has the greatest influence on purchasing decisions with a correlation of r = 0.82, followed by Product Review (r = 0.71) and Discount/Promo Code (r = 0.74). Influencer credibility was also found to be a key factor in influencing consumer trust, with 70% of respondents stating that they only purchase products from influencers they deem trustworthy. Regression analysis showed that the combination of influencer marketing strategies can explain 72.3% of the variation in consumer purchasing decisions (R² = 0.723). These results are in line with Source Credibility Theory, Media Interactivity Theory, and Time Constraints Theory, which explain how trust and interaction influence purchase behavior. The implications of this study suggest that brands and sellers in Shopee should be more active in utilizing influencers with high engagement as well as optimizing interactive features such as Live Shopping to increase sales conversions.